Implementation of Panca Jangka as a Strategy to Develop the Pesantren Gontor - Syamsuri, Syamsuri; Labolo, Sultan Nanta Setia Dien; Firdaus, Iqbal Maulana (The Institute of Research and Service Community IPMAFA Pati, 2023)
Pesantren Darussalam Gontor is one of the oldest and most prominent pesantren in Indonesia, known for its excellent education system and teaching quality. To ensure the sustainability of its development, Gontor implements the Panca Jangka concept as a long-term development plan. This paper employs literature review and content analysis to examine the Panca Jangka concept implemented in Pesantren Gontor and its impacts on the advancement of the boarding school. Relevant data regarding Pesantren Gontor were gathered from various literature. Panca Jangka consists of five key aspects; education and teaching, cadre training, facilities establishment, self-financing, and the welfare of the pesantren community. Its implementation has brought significant positive impacts, such as improvement in educational quality, the establishment of a nationally accredited university, and economic empowerment of the surrounding community. Comprehensively, Panca Jangka plays a vital role in advancing Pesantren Gontor and contributing to the development of pesantren in Indonesia. Gontor becomes a prime example of modern pesantren management that adapts effectively to the changing times.